Efecto del saque en suspensión sobre la construcción del ataque en el voleibol - Urena Espa, A.; Vavassori, R.; Leon Rodriguez, J.; Gonzalez Ortiz, M. (Revista Internacional de Ciencias del Deporte, 2011)
The aim of this study, is to observe the jump serve incidence on the attack phase in the under 14 volleyball. This aspect could influence, as the expert shows, on the right young player`s development. The study consisted in an observation of 2021 plays during the male under 14 Spanish championships. The relationship between jump serve and attack construction possibilities were studied, also the technical way to conclude the point and the result of that play. The results showed a lack of effectiveness to create a team action during the reception phase after a jump serve execution, which means an increase in the difficulty to close the point with a spike or overhead shot. However, the study could not find differences in the comparison of the serve technique and the result of each point. In conclusion, the results bring us to question the jump serve suitability at this age.